2021
DOI: 10.3389/fpsyg.2021.644108
|View full text |Cite
|
Sign up to set email alerts
|

A Balancing Act During Covid-19: Teachers' Self-Efficacy, Perception of Stress in the Distance Learning Experience

Abstract: One of the many drastic changes caused by Covid-19 was the quick implementation of distance learning which represented a great technological challenge to many teachers and students. In fact, Italy ranks 24th amongst the 27-EU member countries in digital competitiveness which testifies to the significant delays and gaps in basic digital skills amongst the population. Based on the difficulties encountered in organizing distance learning, we assumed that teachers' perceived stress increased. Given that transversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 56 publications
4
61
0
2
Order By: Relevance
“…Besides these direct impacts, indirect effects of JD-OT and JR-OT on EE with PIE as mediator (H4a and H4b, respectively) revealed by the empirical results were in agreement with the mediation effect of PIE previously reported ( Huang et al, 2019 ; Rabaglietti et al, 2021 ). In summary, JD-OT undermines PIE but contribute to EE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides these direct impacts, indirect effects of JD-OT and JR-OT on EE with PIE as mediator (H4a and H4b, respectively) revealed by the empirical results were in agreement with the mediation effect of PIE previously reported ( Huang et al, 2019 ; Rabaglietti et al, 2021 ). In summary, JD-OT undermines PIE but contribute to EE.…”
Section: Discussionsupporting
confidence: 91%
“…Using the JD-R model, Huang et al (2019) observed mediating effects of teacher self-efficacy on the relationship between the emotional JD of teaching and well-being of primary school teachers in Hong Kong. Rabaglietti et al (2021) found partial mediation effect of self-efficacy on the relationship between difficulties in organizing distance learning during the pandemic and perceived stress among teachers from European countries. Taken together, these results evidenced the important mediating role of self-efficacy on both positive and negative feelings of teachers in the teaching environment.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 87%
“…Our findings suggest that it is necessary for teachers to implement remote learning while maintaining stimulating activities and promoting social contacts, even if virtual, to support students' motivation and promote their self-efficacy beliefs. These objectives are difficult to achieve in an emergency condition, but they must be considered in planning future academic activities in the post-COVID-19 period (Nguyen et al, 2021;Rabaglietti et al, 2021). In particular, in view of a gradual resumption of a new "normality, " it will be important that remote learning and teaching processes will be planned according to the recommendations on online learning indicated in literature (Kearns, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals can evaluate whether a life event causes stress to themselves only by giving stimulus events a certain meaning through the evaluation process of perception. Perceived stress is a subjective response to specific stress [13]. Psychological research has shown that various stimulus events and unfavorable factors in life can cause psychological confusion or threats to people.…”
Section: Relationship Between Perceived Stress and Anxietymentioning
confidence: 99%